Students' participation in the study circle at the International Islamic University Malaysia (IIUM) in 2010/2011 session - Faizah binti Mohd Fakhruddin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study discusses the issues of students' class participation level in the Study Circle programme and factors that contribute to it. The objectives of the study are to identify the students' class participation level, the factors that are responsible for it and to find ways to increase the effectiveness of the Study Circle programme. The study on the Study Circle programme was conducted from 22nd September 2010 to 11th February 2011, in Semesters 1 and 2, 2010/2011 for a period of four and a half months. For data collection purpose, the study employed the qualitative method using participant observation approach and survey via questionnaire. Two mass lectures and three tutorial sessions of female Study Circle classes during the 2010/2011 academic session were selected for the said purpose. For the survey, ten Malay female students agreed to participate and respond to the questionnaire distributed to them. The findings of the study show that the students' class participation level was not satisfying. There were several factors for this. Interestingly, the study shows that the informants did not perceive factors such as face-saving practice, shyness and peer perception as the responsible factors that determined their class participation level in the Study Circle programme. In actual fact, the most important factor that influenced students' participation was the surrounding factors which include facilitators' attributes, feedback, 2012teaching methods and styles, class size and class time. As for teaching styles and methods, the study found that student-centered approach was preferred in comparison with the teacher-centered approach. The student-centered approach includes the application of problem-based, inquiry-based and project-based learnings of which they strongly believed that the students' class participation would take place actively, particularly when there was a two-way communication between the facilitators and the students. Finally, this study suggests that future research on Study Circle programme needs to be conducted particularly in the Study Circle curriculum which could eventually improve and at the same time ensure active participation from the students. In addition, it is also highly recommended that a comparative study on the above issue be undertaken for the betterment of the Study Circle programme in the future.